Smoking Status and Type 2 Diabetes, and Cardiovascular Disease: A Comprehensive Analysis of Shared Genetic Etiology and Causal Relationship - Chi, Yanna; Wang, Xinpei; Jia, Jinzhu; Huang, Tao (Frontiers in Endocrinology, 2022)
Objective: This study aimed to explore shared genetic etiology and the causality between smoking status and type 2 diabetes (T2D), cardiovascular diseases (CVDs), and related metabolic traits. Methods: Using summary statistics from publicly available genome-wide association studies (GWASs), we estimated genetic correlations between smoking status and T2D, 6 major CVDs, and 8 related metabolic traits with linkage disequilibrium score regression analysis (LDSC), identified shared genetic loci with large-scale genome-wide cross-trait meta-analysis, explored potential shared biological mechanisms with a series of post-GWAS analyses, and determined causality with Mendelian Randomization (MR). Results: We found significant positive genetic associations with smoking status for T2D (Rg=0.170, P=9.39×10-22), coronary artery disease (CAD) (Rg=0.234, P=1.96×10-27), myocardial infarction (MI) (Rg=0.226, P=1.08×10-17), and heart failure (HF) (Rg=0.276, P=8.43×10-20). Cross-trait meta-analysis and transcriptome-wide association analysis of smoking status identified 210 loci (32 novel loci) and 354 gene–tissue pairs jointly associated with T2D, 63 loci (12 novel loci) and 37 gene–tissue pairs with CAD, 38 loci (6 novel loci) and 17 gene–tissue pairs with MI, and 28 loci (3 novel loci) and one gene–tissue pair with HF. The shared loci were enriched in the exo-/endocrine, cardiovascular, nervous, digestive, and genital systems. Furthermore, we observed that smoking status was causally related to a higher risk of T2D (β=0.385, P=3.31×10-3), CAD (β=0.670, P=7.86×10-11), MI (β=0.725, P=2.32×10-9), and HF (β=0.520, P=1.53×10-6). Conclusions: Our findings provide strong evidence on shared genetic etiology and causal associations between smoking status and T2D, CAD, MI, and HF, underscoring the potential shared biological mechanisms underlying the link between smoking and T2D and CVDs. This work opens up a new way of more effective and timely prevention of smoking-related T2D and CVDs.